Determinants of Organizational Culture and Its Impact on Employee Performance at PT. AHI - Da'wat, Mujibu; Nuraeni, Nuraeni; Yusuf, M (International Journal of Advanced Multidisciplinary, 2023)
The study of organizational culture, which is believed to have a significant impact on companies, is an intriguing field of research. It aims to unravel the realities and intricacies of organizational culture, leadership, career advancement, and employee performance at PT AHI. To conduct this study, a survey method with a quantitative approach was employed. The researcher observed and formulated a series of statements with multiple-choice options to gather numerical responses through questionnaires. A total of 98 employees participated as respondents, and the collected data was analyzed using the Structural Equation Modeling (SEM) technique with smartPLS software. The findings indicate that leadership (X1) and career development (X2) have a positive and significant influence on organizational culture (Y). The R-square value of 0.519 suggests that organizational culture (Y) is influenced by leadership (X1) and career development (X2). Furthermore, employee performance (Z) is concurrently influenced by organizational culture (Y), leadership (X1), and career development (X2), with an R-square value of 0.681.